Physiological effects of spirulina supplementation during lactate threshold exercise at simulated altitude (2,500 m): a randomized controlled trial - Tom Gurney; James Brouner; Owen Spendiff (Journal of the International Society of Sports Nutrition)
Background Existing literature indicates that spirulina supplementation can improve a variety of blood morphological parameters (such as hemoglobin) in healthy and clinical populations. Given the importance of hemoglobin for endurance exercise, particularly at altitude, this study aimed to investigate whether spirulina supplementation can improve blood morphological parameters in healthy cyclists and positively influence physiological variables when completing a lactate threshold test at simulated moderate altitude (2,500 m).Methods Twenty (18 male; 2 female) healthy participants (Mean  ±  SD; Age 37   ±   9 years, Stature 181   ±   6 cm, Mass 81   ±   9 kg, [Formula: see text]O2max 51.8   ±   7.8 ml·kg-1·min-1) ingested 6 g/day of spirulina or placebo for 3-weeks in a double-blinded randomized counter-balanced cross-over design, then completed a lactate threshold test at simulated moderate altitude, with a 14-day washout period between trials.Results Following spirulina supplementation, heart rate at the lactate threshold was significantly lower in comparison to placebo supplementation (spirulina = 152   ±   11 b.min −1 vs. placebo = 155   ±   12 b.min −1, p < 0.05). No other physiological variables (Watts, RER, RPE, VO2) were significantly different (p > 0.05) at the calculated threshold, or during the first four lower stages. Red Cell Distribution Width significantly increased following spirulina supplementation in comparison to placebo (spirulina = 13.3   ±   0.9 % vs. placebo = 12.5   ±   0.7 %, p < 0.05). Plateletcrit significantly decreased following spirulina supplementation (spirulina = 0.288   ±   0.032 vs. placebo = 0.293   ±   0.050, p < 0.05). No other blood morphological parameters changed (p > 0.05).Conclusion In conclusion, three weeks of spirulina supplementation at 6 g/day reduced heart rate during a lactate threshold test at a simulated moderate altitude (2,500 m), but did not produce additional physiological or hematological benefits.